2007
DOI: 10.1177/15648265070283s304
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Indicators for Assessing the Adequacy of Population Zinc Intakes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 73 publications
2
48
0
Order By: Relevance
“…This said, our results were not dissimilar to those of Pathak et al [11], who reported 75.7 % of nulliparous rural Indian women had zinc intakes <50 % of the recommended dietary allowance (RDA), although this does not give an estimate of the proportion of low zinc intake. However, a review by Hotz [32] estimated that 50 % of women had inadequate zinc intakes or intakes below the EAR in the study by Pathak et al The present study estimated that 72 % of rural and 82 % of tribal women were at elevated risk of low zinc intakes. Regardless of the actual prevalence, the true prevalence in this population will be well above the 25 % the IZiNCG cutoff, thus of public health concern with intervention advised [1].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This said, our results were not dissimilar to those of Pathak et al [11], who reported 75.7 % of nulliparous rural Indian women had zinc intakes <50 % of the recommended dietary allowance (RDA), although this does not give an estimate of the proportion of low zinc intake. However, a review by Hotz [32] estimated that 50 % of women had inadequate zinc intakes or intakes below the EAR in the study by Pathak et al The present study estimated that 72 % of rural and 82 % of tribal women were at elevated risk of low zinc intakes. Regardless of the actual prevalence, the true prevalence in this population will be well above the 25 % the IZiNCG cutoff, thus of public health concern with intervention advised [1].…”
Section: Discussionmentioning
confidence: 62%
“…The proportion of women with inadequate zinc intakes in the present study was 78 % (i.e., using the IZiNCG cutoff) although this should be interpreted with caution. IZiNCG suggests that usual intakes be adjusted for within-subject day-to-day variability, which narrows the distribution of intakes [32]. This is typically done by collecting a repeat diet recall and adjusting for day-to-day within-subject variation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the data used by the IZiNCG were based only on total-diet tracer studies that represented typical diets consumed by populations irrespective of geographic location and that included studies on men and women; details of their derivation are given elsewhere (13,119).…”
Section: Classifying Diets According To Zn Bioavailability and Develomentioning
confidence: 99%
“…(ii) The type of intervention was defined as zinc salts given as tablets or syrups orally to provide at least 1 RDA of elemental zinc for at least a period of 14 days introduced within one month of birth. The RDAs for zinc in low birth weight breast fed infants have not been defined [6,7]. However, the suggested average dietary intakes (ADI, which are invariably lower than RDA) for infants in the age group of 0 to 6 months are 2 mg(6) and it is believed that the requirements would be higher in LBW infants.…”
Section: Discussionmentioning
confidence: 99%